TAX AWARENESS, MODERN TAX ADMINISTRATION SYSTEM AND TAX SANCTIONS AGAINST TAXPAYER COMPLIANCE - Saraswati, Zulaicha Efrita; Masitoh, Endang; Dewi, Riana Rachmawati (eBA Journal: Journal Economics, Bussines and Accounting, 2018)
The purpose of this research is to know the influence of the consciousness of tax, the tax administration system and modern taxation sanctions against taxpayer compliance. The sample used in this study the taxpayer in the city of Surakarta. The technique of sampling is done using a purposive sampling of the dwarf. The sample of respondents in the study were 40 tax payers. Methods of analysis used was multiple linear regression analysis. Results of the study the feasibility test model (F test) shows that the independent variable (the awareness of tax, the tax administration of the modern sisem and tax penalties) influential and significantly to the dependent variables (compliance with tax payers).  The results of the research hypothesis test (test t) indicates that the variable tax consciousness and modern tax administration system and significant effect against taxpayer compliance, while variable tax sanctions had no effect and no significant against taxpayer compliance.